Comparison of the Screening Practices of Unaffected Noncarriers under 40 and between 40 and 49 in BRCA1/2 Families. Issue 4 (25th January 2013) - Duprez, Christelle; Christophe, Véronique; Milhabet, Isabelle; Krzeminski, Aurélie; Adenis, Claude; Berthet, Pascaline; Peyrat, Jean‐Philippe; Vennin, Philippe
Abstract: This study aimed to 1) compare the cancer screening practices of unaffected noncarrier women under 40 and those aged 40 to 49, following the age‐based medical screening guidelines, and 2) consider the way the patients justified their practices of screening or over‐screening. For this study, 131 unaffected noncarriers—77 women under age 40 and 54 between 40 and 49, all belonging to a BRCA1/2 family—responded to a questionnaire on breast or ovarian cancer screenings they had undergone since receiving their negative genetic test results, their motives for seeking these screenings, and their intentions to pursue these screenings in the future. Unaffected noncarriers under age 40 admitted practices that could be qualified as over‐screening. Apart from mammogram and breast ultrasounds, which the women under 40 reported seeking less often, these women's screening practices were comparable to those of women between 40 and 49. Cancer prevention and a family history of cancer were the two most frequently cited justifications for pursuing these screenings. We suggest that health care professionals discuss with women under 50 the ineffectiveness of breast and ovarian cancer screenings so that they will adapt their practices to conform to medical guidelines and limit their exposure to the potentially negative impacts of early cancer screening.